Analisis Determinasi Kinerja Karyawan: Kepemimpinan dan Remunerasi - Sudiharto; Feby Arma Putra (UPT Publikasi Ilmiah Unisba, 2026)
Abstract. The purpose of this study is to examine how organizational culture, compensation, and transformational leadership affect employee performance at PT. XYZ Head Office. A quantitative approach with a descriptive study design is the research methodology used. Multiple linear regression was used to evaluate the data after questionnaires were administered to 100 employees as the research sample. The results showed that compensation, organizational culture, and transformational leadership all significantly and positively affect employee performance. The three independent variables explained 74% of the variation in employee performance, with other factors outside the research model influencing the remaining 26%, according to a coefficient of determination value of 0.740. Employee performance was significantly influenced by organizational culture (t = 2.970), compensation (t = 4.279), and transformational leadership (t = 3.262), according to the results of the partial test (t-test). These results suggest that strengthening organizational culture, providing adequate compensation, and improving the quality of transformational leadership may be useful tactics to improve employee performance at PT. XYZ. Abstrak. Tujuan penelitian ini adalah untuk menguji bagaimana budaya organisasi, kompensasi, dan kepemimpinan transformasional memengaruhi kinerja pekerja di Kantor Pusat PT. XYZ. Pendekatan kuantitatif dengan desain studi deskriptif adalah metodologi penelitian yang digunakan. Regresi linier berganda digunakan untuk mengevaluasi data setelah kuesioner diberikan kepada 100 karyawan sebagai sampel penelitian. Hasil penelitian menunjukkan bahwa kompensasi, budaya organisasi, dan kepemimpinan transformasional semuanya secara signifikan dan positif memengaruhi kinerja pekerja. Tiga variabel independen tersebut menjelaskan 74% variasi kinerja karyawan, dengan faktor-faktor lain di luar model penelitian memengaruhi 26% sisanya, menurut nilai koefisien determinasi sebesar 0,740. Kinerja karyawan secara signifikan dipengaruhi oleh budaya organisasi (t = 2,970), kompensasi (t = 4,279), dan kepemimpinan transformasional (t = 3,262), menurut hasil uji parsial (t-test). Hasil ini menunjukkan bahwa penguatan budaya organisasi, pemberian kompensasi yang memadai, dan peningkatan kualitas kepemimpinan transformasional mungkin merupakan taktik yang berguna untuk meningkatkan kinerja karyawan di PT. XYZ.